How do consumers from developed regions evaluate global brands from emerging countries? An investigation from the perspective of global–local identity. Issue 1 (3rd September 2018) - Guo, Xiaoling; Hong, Ying-yi
Abstract : Purpose: While an increasing number of global brands are of emerging country origin, research about emerging global brands remains scare. The purpose of this paper is to provide the first theoretical effort to understand how consumers in the developed regions evaluate global brands from emerging countries. Building on globalization and social identity theory, the paper aims to shed light on the effect of global identity on consumer attitude toward emerging global brands, the process of such effect, and the boundary condition for it as well. Design/methodology/approach: The authors used two non-student surveys in the USA and UK in which respondents' global identity was measured and two laboratory experiments in which respondents' global identity was primed. The operationalization of dependent variables is also divergent, either directly measuring attitude toward the global brands from developing countries or measuring consumer relative evaluation. Convergent results were reported from four studies. Findings: The results show that when consumers' global (vs local) identity is accessible, those from developed regions will show more favorable evaluations of global brands from emerging countries. And this effect is mediated by the positive association between global identity and globalization. Further, this effect emerged when consumers view global and local cultures as compatible with each other but disappeared when consumers view global and local cultures as oppositional to each other. Practical implications: The findings have practical implications for global brand marketers from emerging economies to enter developed country markets, and to make their brands real global. Specifically, global identity consumers should be targeted and the compatible view of global and local cultures should be pronounced. Originality/value: Focusing on global brands from emerging countries, this paper examines the global identity effect in developed country markets for the first time. The finding add new knowledge to the literature of globalization, global branding, and assimilation effect of global identity, and help to reconcile the heated debate on whether country of origin is still relevant to the globalized world.